Transformasi Kesenian Marhaban Oleh Grup Jami’ul Khoir Pekan Labuhan untuk Promosi Budaya dan Pengembangan Ekonomi Kreatif berbasis Kearifan Lokal Masyarakat Pesisir - Evianty, Rina; Hirza, Herna; Sari, Risnovita; Destiara, Ria Fuji (Jurnal Gema Ngabdi, 2025)
The marhaban art tradition in Pekan Labuhan represents a coastal cultural heritage rich in religious, social, and historical values. However, limited regeneration, weak digital promotion, and a lack of innovation have contributed to its declining presence. This community engagement program aims to revitalize the Jami’ul Khoir group through intergenerational training, the development of innovative performance models, and the use of digital technologies for documentation and promotion. The methods employed include community outreach, artistic and media training, the application of innovative musical arrangements, digital content production, and ongoing mentorship. The program’s outcomes include increased youth participation, the creation of contemporary marhaban arrangements, the establishment of a digital archive, and the strengthening of the creative economy through merchandise production. Ultimately, this initiative not only enhances the visibility of marhaban but also reinforces coastal cultural identity and creates new economic opportunities rooted in local wisdom.